O simulador virtual de astronomia nas aulas de física: uma reflexão sobre seu uso no Ensino Médio - Rodrigues, Nádia Cristina Moreira (2020)
The present work on the use of Virtual Astronomy Simulators in High School Physics classes, presents the results of experimental and quantitative research, whose main objective was to prove the effectiveness of using these simulators in Astronomy Teaching. 193 students participated in this study, from six selected classes, two for each year of high school at Colégio Modelo Luís Eduardo Magalhães in Feira de Santana in 2019. Regarding the use or not of simulation, the classes were called: Experimental Class (TE) and Control Class (TC), respectively. Simulators from the University of Nebraska-Lincoln (UNL) were used, except for the theme Eclipses whose simulator was from the Federal University of Rio Grande do Sul (UFRGS). For the first year, simulators were applied with the themes: Apparent Movement of the Sun and Seasons. In the second year: Moon phases and eclipses. For the third year: Planetary Orbits and Planetary Configurations. This study discussed the effectiveness of using computer simulators for teaching astronomy, as previous organizers, based on David Ausubel's Theory of Meaningful Learning, using the application of Diagnostic Assessments and structured interview. The results of the quantitative research, obtained with the analyzes: percentages and statistics with t-test and p-value, were favorable to the use of computer simulators, indicating the occurrence of significant learning by TE students, thus validating the teaching strategy developed based on the concept of previous organizers. Therefore, at the end of the application of the aforementioned research, a paradigm was generated as an Educational Product, linked to this dissertation entitled: Didactic Scripts for use of Virtual Simulators with a focus on Astronomy.